Power-scalable sub-100-fs Tm laser at 2.08 μm. (23rd September 2021) - Wang, Li; Chen, Weidong; Zhao, Yongguang; Yang, Hanlin; Jing, Wei; Pan, Zhongben; Huang, Hui; Liu, Jiachen; Bae, Ji Eun; Rotermund, Fabian; Loiko, Pavel; Mateos, Xavier; et al.
Abstract: We report on a power-scalable sub-100-fs laser in the 2-μm spectral range using a Tm 3+ -doped 'mixed' (Lu, Sc)2 O3 sesquioxide ceramic as an active medium. Pulses as short as 58 fs at 2076 nm with an average output power of 114 mW at a pulse repetition rate of approximately 82.9 MHz are generated by employing single-walled carbon nanotubes as a saturable absorber. A higher average power of 350 mW at 2075 nm is obtained at the expense of the pulse duration (65 fs). A maximum average power of 486 mW is achieved for a pulse duration of 98 fs and an optical conversion efficiency of 22.3%, representing the highest value ever reported from sub-100-fs mode-locked Tm lasers.